(untitled) (Sains Humanika, 2013)
Producing high quality human capital is the main agenda in our education system. Therefore, the intent should be transformed with full commitment, compassionate and dedicated by every educator. However, lack awareness of the real meaning and aim of education among trainee educator will reduce our possibility to achieve the agenda. Therefore, the purpose of this study is to determine strength of educator‟s soul development among final year students (trainee educator) from Faculty of Education UTM. Quantitative research design has been used to collect data from 89 respondents which is the whole population of study. The reliability value 0.93 has been obtained using Cronbach Alpha and the value shows that the research instrument is reliable to fulfill the purpose of this study. The finding shows that, the strength of educator‟s soul development among final year students is moderately high with mean value at 3.86. The finding also shows that trainee educator‟s level of attentiveness toward education aim which is to develop human potential based on universal value belief and devotion to God obtain the lowest mean 3.62 which is at the moderate level. Therefore, there is essential to put more effort to strengthen trainee educators‟ attentiveness towards the real aim of education.